2020
DOI: 10.3390/ijerph17145261
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks’ Engagement During the COVID-19 Pandemic in Spain: Health Media vs. Healthcare Professionals

Abstract: An increased use of social networks is one of the most far-reaching consequences of the COVID-19 pandemic. Aside from the traditional media, as the main drivers of social communication in crisis situations, individual profiles have emerged supported by social networks, which have had a similar impact to the more specialized communication media. This is the hypothesis of the research presented, which is focused on health communication and based on a virtual ethnography methodology with the use of social metrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 27 publications
2
63
0
6
Order By: Relevance
“…To ensure user confidence, on 17 March 2020 the major social network companies declared that they would work closely together to combat false and misinformation and promote information from official sources [ 21 ]. Four levels of social network engagement have been acknowledged: (1) observer, (2) follower, (3) participant and (4) defender which can be further condensed into two levels of: passive engagement (level 2) and cognitive participative engagement (levels 3 and 4) [ 22 ]. Of the CANZ posts, infographics were engaged with by users more extensively than video resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure user confidence, on 17 March 2020 the major social network companies declared that they would work closely together to combat false and misinformation and promote information from official sources [ 21 ]. Four levels of social network engagement have been acknowledged: (1) observer, (2) follower, (3) participant and (4) defender which can be further condensed into two levels of: passive engagement (level 2) and cognitive participative engagement (levels 3 and 4) [ 22 ]. Of the CANZ posts, infographics were engaged with by users more extensively than video resources.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the infographics, the videos had less engagement and required longer viewing times (7–55 min) with the highest average watch time being 17 s. Interestingly, TikTok, a video sharing platform that has gained prominence during the COVID-19 pandemic uses a short-form format of 15 s [ 25 ]. Pérez-Escoda and colleagues highlight that social audiences need to be part of the media flow [ 22 ] which was reinforced by Raamkumar and colleagues, who observed that Facebook users engaging with content from health authorities were more likely to share a post aiding the dissemination of information than they were to react or comment [ 26 ]. It could be speculated that the anticipated uptake by one’s followers influences how users interact with content and in this respect those resources that require less time to view may be perceived as having better uptake by other social network users gaining more positive reactions (e.g., like, care, love), comments and shares.…”
Section: Discussionmentioning
confidence: 99%
“…The role of social media in spreading misleading health information is not new [ 3 ], but the COVID-19 crisis has shown the critical impact of this new information environment [ 4 ]. Many studies have focused on and are still focusing on how the disintermediated role of social media may foster misinformation: Scholars studying Iran [ 5 ] and Spain [ 6 ], stress how social media spread rumors, others [ 7 ] try to analyze the structure of this infodemic, or concentrate on the effect of media exposure [ 8 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…В условиях принудительной по своей сути цифровизации становится важным внимательно исследовать структурные трансформации в сфере массового информационного потребления в интернет-пространстве. Неслучайно значительное число ученых -социологов, политологов, коммуникативистов уделяют сегодня особое внимание проблемам, связанным с изменениями, происходящими в цифровой среде в аспекте изменения структуры и объемов информационного потребления [Volodenkov, Pastarmadzhieva 2020;Pérez-Escoda et al 2020;Iivari et al 2020;Agostino et al 2020;Hussain 2020].…”
Section: Introductionunclassified